The Effect of Problem-Based Learning Model Assisted by PhET Media on Students' Critical Thinking Skills - Aisyah, St. Nur; Kosim, Kosim; Gunawan, Gunawan; Gunada, I Wayan (Indonesian Journal of STEM Education, 2024)
This study aimed to examine the effect of a problem-based learning (PBL) model incorporating PhET Interactive Simulations on students' critical thinking skills. A quasi-experimental design, specifically an untreated control group design with pretest and posttest, was employed. The population comprised all eleventh-grade science students at SMAN 3 Mataram. Purposive sampling was used to select two classes: XI MIPA 3 as the experimental group and XI MIPA 6 as the control group. The research instrument consisted of a seven-item essay test designed to measure critical thinking skills. The instrument underwent validity, reliability, discriminating power, and difficulty level testing. Data analysis was performed using an independent samples t-test with a significance level of 5%. The results indicated a statistically significant difference between the experimental and control groups. Therefore, it can be concluded that the problem-based learning model with PhET media effectively enhances students' critical thinking skills.